2013
DOI: 10.1038/jcbfm.2013.45
|View full text |Cite
|
Sign up to set email alerts
|

TIMP-1 Attenuates Blood–Brain Barrier Permeability in Mice with Acute Liver Failure

Abstract: Blood–brain barrier (BBB) dysfunction in acute liver failure (ALF) results in increased BBB permeability that often precludes the patients from obtaining a life-saving liver transplantation. It remains controversial whether matrix metalloproteinase-9 (MMP-9) from the injured liver contributes to the deregulation of BBB function in ALF. We selectively upregulated a physiologic inhibitor of MMP-9 (TIMP-1) with a single intracerebroventricular injection of TIMP-1 cDNA plasmids at 48 and 72 hours, or with pegylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…Future work is required to examine this hypothesis as well as to evaluate the function and stability of the choroid plexus and arachnoid membrane in post-mortem and imaging studies in schizophrenia. Results from studies in the fields of stroke, brain injury and liver failure, have shown that such compounds as melatonin, idazoxan, an imidazoline 2 receptor ligand, and inhibitors of matrix metalloproteinases may protect against blood-brain barrier and choroid plexus pathologies induced by a variety of methods in cell culture experiments and rodent models (Chen et al, 2013; Turgut et al, 2007; Verma et al, 2010; Wang et al, 2014). Thus, based on this work, therapies aimed to remove the antigenic source and to normalize endothelial barrier functions may be applicable treatment modalities to explore for safety and efficacy trials in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Future work is required to examine this hypothesis as well as to evaluate the function and stability of the choroid plexus and arachnoid membrane in post-mortem and imaging studies in schizophrenia. Results from studies in the fields of stroke, brain injury and liver failure, have shown that such compounds as melatonin, idazoxan, an imidazoline 2 receptor ligand, and inhibitors of matrix metalloproteinases may protect against blood-brain barrier and choroid plexus pathologies induced by a variety of methods in cell culture experiments and rodent models (Chen et al, 2013; Turgut et al, 2007; Verma et al, 2010; Wang et al, 2014). Thus, based on this work, therapies aimed to remove the antigenic source and to normalize endothelial barrier functions may be applicable treatment modalities to explore for safety and efficacy trials in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Dissection of this process revealed that MMP-3 directly activates EMT [Lochter et al 1997; Lochter et al 1997] by activating alternative splice pathways which result in the expression of Rac1b [Radisky et al 2005; Pelisch et al 2012; Cichon et al 2015]. Rac1b is an activated splice variant with unique tumor-promoting activities [Orlichenko et al 2010], which stimulates EMT by increasing levels of cellular reactive oxygen species [Radisky et al 2005; Nelson et al 2008; Cichon and Radisky 2014], through a process that depends upon cell-ECM interactions [Lee et al 2012; Batra et al 2013; Chen et al 2013]. Thus, MMPs can stimulate invasion through both extrinsic (ECM-targeting) and intrinsic (cell phenotype alteration) processes.…”
Section: Tumorigenic Processes Activated By Mmps In Breast Cancermentioning
confidence: 99%
“…A final challenge, given the short serum half-life of unmodified recombinant TIMPs in vivo [Batra et al 2012], will be to develop formulations and delivery methods capable of achieving sustained therapeutic concentrations. Promising approaches reported to date include PEGylation [Batra et al 2012; Chen et al 2013], fusion to serum albumin [Kang et al 2007; Lee et al 2011], nanoparticle delivery [Chaturvedi et al 2012; Chaturvedi et al 2014], and encapsulation in peptide hydrogels [Chowdhury et al 2017] to enhance recombinant TIMP availability, stability and efficacy in vivo .…”
Section: Developing Mmp Inhibitors For Therapeutic Applicationsmentioning
confidence: 99%
“…Several studies have demonstrated that increased circulating MMP-9 level is associated with the BBB permeability changes in hemorrhagic transformation in stroke after thrombolytic therapy [34,35] and in acute liver failure [36]. These findings indicate that circulating MMP-9 level may reflect the status of BBB permeability.…”
Section: Discussionmentioning
confidence: 62%